Reformar el art. 70 de la Ley Orgánica De Defensa Del Consumidor a fin de incrementar la sanción por la publicidad engañosa e incluir la figura de la reincidencia, ya que se vulneran los derechos del consumidor - Campos Sandoval, Elsa Susana (2016)
This paper aims to address the issue of misleading advertising in today's society, related to the rights of consumers and users to obtain clear and detailed information on the goods and services that are offered in the market. To this end we will begin with the development of the evolution of consumer law, then head into the applicable rules to the particular in our country and culminating with recent jurisprudence cases in which it was considered that resorted to this technique to capture Contracting possible. In this research study the fundamental issues of the Act, in relation to the historical and doctrinal and the legal and procedural aspects; and the reforms, the gains made since the enactment of the law in our country; Organic Consumer Protection Act makes no exceptions in terms of its scope and states that all relationships between suppliers and consumers, and also the rights and obligations contained in the text does not exclude or oppose are included to standards of environmental protection, sustainable development or related. Only make exception to the rules of Chapter X Protection of health and safety, which are extra address the special rules governing the provision of certain goods and services which by its nature must be subject to special treatment. This work certainly has the purpose to contribute, through research and analysis, to better understand the deceptive or abusive Organic Consumer Protection Act and its regulations regulating advertising and its content, advertising bans, considered the Commercial basic information. The amendment to the Act to increase the penalties for misleading advertising to include the figure of recidivism While there are standards of consumer protection in each of the areas of the economy that are regulated in particular, there should also be rules which tend to apply consumer protection in both the quality of goods and services, advertising, product information, sales terms and the distance sales, among others. The special schemes and the general rule should therefore be complementary and not contradictory. It is therefore important to make a thorough study of the Organic Law Consumer Protection: find the reason for its creation, its content, and the way in which the various sanctions and enforcement are contemplated. The Constitution of the Republic of Ecuador, approved in a referendum by the Ecuadorian people, was published in the Official Gazette No. 449 of October 20, 2008, when it took full effect, it recognizes the rights of consumers in addition to constitutionalises some rights governed by the Organic Law on Consumer Protection, are now covered by clear and concrete form in the Constitution, that legally is called the "constitutionalization" (rights that were previously in a law and now goes to a constitution). Another important point of the research work are surveys and interviews held to different professional authorities who have experience in addition to being closer to the subject it is relevant to know that different opinions and analysis are known. In addition I was allowed to give recommendations by the conclusions of the entire research work and above all propose to reform the Organic Law of the consumer as to the penalty for the offense, thus ensuring the rights of consumers